Pop andino en el espacio digital: análisis de las ideologías lingüístico-raciales y propuesta tecnológica contra los hate speech racistas en redes sociales - Cáceres de la Cruz, Faustina (2025)
The article analyses the representation in virtual spaces of the Andean subject subordinated to ‘Andean pop’, a genre established by Milena Wharton, which aspires to consolidate a contemporary Andean identity through a hybrid and novel aesthetic, often wrapped in linguistic-racial ideologies that guide the way we interact with other members of our society. Through a work of collecting samples in social networks (Facebook, Instagram and X), the research revealed how certain users resort to racist hate comments to delegitimize this emerging musical genre by perceiving it as an ‘inauthentic’ representation of Quechua culture. For this reason, the development of a Google extension called ‘InkluApp’ is proposed as a concrete solution to mitigate the effects of online discrimination which, in its turn, reinforces the relevance of IT tools that contribute to counteract racist hate speech. In this way, a link is established between the study of the ideologies underpinning racist hate speech and a technological intervention that seeks to foster a fair and inclusive representation of the Andean individual in the digital age.